The dogs of Christmas [large type] - Cameron, W. Bruce (Wheeler Publishing, 2013)
While nursing a broken heart, Josh Michaels is outraged when a neighbor abandons his very pregnant dog, Lucy, at Josh's Colorado home. Though he's never had a dog before, Josh is determined to do the best he can for Lucy-- and her soon-to-arrive puppies. He calls the local animal shelter for help, and meets Kerri, who teaches Josh how to care for Lucy's tiny puppies and gets them ready to be adopted through the shelter's "Dogs of Christmas" program.